Eight-Year Outcomes of Implantation of Posterior Chamber Phakic Intraocular Lens With a Central Port for Moderate to High Ametropia - Kamiya, Kazutaka; Shimizu, Kimiya; Takahashi, Masahide; Ando, Wakako; Hayakawa, Hideki; Shoji, Nobuyuki (Frontiers in Medicine, 2021)
Purpose: To assess the 8-year clinical outcomes of implantation of an implantable collamer lens (ICL) with a central port (KS-Aquaport; EVO-ICL) for moderate to high myopia and myopic astigmatism. Methods: This retrospective study comprised a total of 177 eyes of 106 patients with spherical equivalents of −7.99 ± 3.33 D [mean ± standard deviation], who underwent EVO-ICL implantation. We evaluated the safety, efficacy, predictability, stability, and adverse events of the surgery, at 1 month, and 1, 2, 4, 6, and 8 years postoperatively. Results: The logarithm of the minimal angle of resolution (LogMAR) uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) were −0.07 ± 0.17 and −0.20 ± 0.09, respectively, at 8 years postoperatively. The safety and efficacy indices were 1.18 ± 0.24 and 0.89 ± 0.28, respectively. At 8 years, 83 and 93% eyes were within ± 0.5 D and ± 1.0 D of the targeted correction, respectively. Change in manifest refraction from 1 month to 8 years postoperatively was −0.13 ± 0.30 D. Three eyes (1.7%) that developed cataracts had a slight pre-existing peripheral anterior subcapsular cataract formation required simultaneous ICL extraction and cataract surgery at 2 or 3 years or ICL size change (1 size up) at 7 years postoperatively. We found that neither significant intraocular pressure (IOP) rise (including pupillary block) nor significant endothelial cell loss occurred in any case throughout the 8-year observation period. Conclusions: Current ICL implantation with central port technology offered good continuous outcomes for all measures of safety, efficacy, predictability, and stability for correcting moderate to high myopic errors over a long period, thereby suggesting its long-term viability as a surgical approach for the treatment of such eyes.